Peace Education Insightful Material Design - Farah Dina Insani (AIUA Journal of Islamic Education, 2020)
This research explores the design of PAI-oriented peach education material. The goal is to encourage student participation in making decisions and solving a problem at hand. In this study the authors use the method of data collection with the method of documentation, as is the case in data collection techniques in library research. The documentation method is the method carried out by researchers of objects or documents such as magazines, books, minutes of diary meetings and so on. The object of study in this article focuses on the understanding, nature, characteristics, and objectives of peace education. His findings show that education with an educational perspective The concept of Peace Education is essentially contrary to murder, violence, persecution, terrorism and the like. Peace education seeks to prevent violence and create peace through education.